THU0415 MELTING OF TOPHI WITH LOCAL STEROIDS IN CHRONIC TOPHACEOUS GOUT: AN OBSERVATIONAL STUDY. (2nd June 2020) - Bhadu, D.; Vyas, S.; Kumar, U.
Abstract : Background: Chronic tophaceous gout is usually difficult to treat with urate lowering therapy (ULT) [1]. Faster resolution of tophi has been seen with use of pegloticase [2], but this drug is costly and not widely available. Local steroid use is recommended in acute gouty arthritis but its role in reduction of tophi has not been studied. This study was aimed to see the effect of local steroids in tophi resolution. Objectives: To study the change in size of gouty tophi with local steroid injection compared to conventional treatment. Methods: Four crystal proven chronic tophaceous gout patients with multiple tophi were screened and enrolled in the study after taking informed consent. Total 12 tophi in 4 patients were imaged by using Duel Energy Computed Scan (DECT) for their size and volume. All 4 patients were treated with ULT as per recommended dose to achieve target serum uric acid (SUV) level. Six tophi were treated with local steroids injection (methylprednisolone acetate) at two months interval till complete resolution of tophi. Dose of steroid varied from 10 mg to 40 mg depending upon tophi size but subsequent repeat doses were same in each tophi. Six tophi not treated with local steroid served as internal control in the same patients. All 4 patients were followed up regularly in out-patient department to monitor treatment response and local side effects if any. Results: All 4 patients achieved target SUV (<356 µmol/L) at three months of follow up. Six tophi which were treated with local steroids injection clinically had marked reduction in size at 7-12 months of follow up [Table-1], while other 6 tophi which served as internal control had no clinically significant change in size and volume of tophi. DECT was repeated in the same settings to confirm the clinical findings. DECT revealed near complete resolution of 5 tophi [Image-1], and 50% reduction in size of one tophi. Six tophi which were not treated with local steroid had no significant reduction in size in DECT as well. Only side effect noted was skin discoloration in 5 out of 6 injected sites, none of the tophi had infection. Conclusion: Interestingly this is the first such study to document the use of local steroid in tophi. Thus intralesional steroids can be alternative to pegloticase or surgery where faster dissolution of tophi is required. This observation needs to be explored in large number of patients to calculate the total dose requirement of steroid as per volume and urate burden of tophi. Possible explanation of melting tophi with steroids is breaking down outer fibrous layer of tophi by local steroids which might be acting as barrier in dissolution of urate crystals with ULT. References: [1]Dalbeth N, House ME, Horne A et al. Prescription and dosing of urate-lowering therapy, rather than patient behaviours, are the key modifiable factors associated with targeting serum urate in gout. BMC Musculoskelet Disord 2012;13:174 [2]Baraf HS, Becker MA, Gutierrez-Urena SR, et al: Tophus burden reduction with pegloticase: results from phase 3 randomized trials and open-label extension in patients with chronic gout refractory to conventional therapy. Arthritis Res Ther 15:R137, 2013 Disclosure of Interests: None declared